Penataan Penataan Kewenangan KPU dan Bawaslu dalam Melakukan Pengawasan dan Menangani Sengketa Proses Pemilu - Hananto Widodo; Dicky Eko Prasetio (Perspektif Hukum, 2021)
The general election organizing body is an institution designed to have a check and balance function so that it is oriented towards realizing a democratic process in accordance with the constitution. In Indonesia, the institution responsible for the implementation of the general election is not only the General Election Commission but also other institutions, such as the General Elections Supervisory Board and the Honorary Council for General Election Organizers. This study seeks to initiate the structuring of the General Election Commission and the General Elections Supervisory Agency in supervising and handling disputes over the General Election process. This research is a legal research. This research uses a statutory approach, a conceptual approach, and a historical approach. The results of this study indicate that if it is made in stages, if the election participants do not accept the General Election Commission's attitude, then the election participants can appeal to the General Elections Supervisory Agency, and if there are parties who cannot accept the decision of the General Elections Supervisory Board, then the those who cannot accept it should file a lawsuit to the State Administrative High Court.